2011
DOI: 10.1097/rli.0b013e3182174fad
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Angiogenesis Imaging of Orthotopic Bladder Tumors in Mice Using a Selective Magnetic Resonance Imaging Contrast Agent Containing VEGF121/rGel

Abstract: Synthesized VEGF121/rGel-MNPs as targeted MR imaging contrast agents can be specifically delivered to tumors and bind to KDR-expressing angiogenic tumor vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…However, the oxidation is much facilitated in aqueous solutions (vide infra). In order to examine the pH-dependent stability of the formed MnO@Mn 3 O 4 nanourchin, we placed MnO nanourchins surface-modified with carboxylated amphiphilic polysorbate 80 molecules [10] in phosphate-buffered saline (PBS) solutions of various pH values. While the nanourchin is very stable at pH values above 7, the MnO core is easily dissolved at lower pH conditions (pH 4-6) to give a hollow Mn 3 O 4 nanourchin ( Figure S13 in the Supporting Information).…”
mentioning
confidence: 99%
“…However, the oxidation is much facilitated in aqueous solutions (vide infra). In order to examine the pH-dependent stability of the formed MnO@Mn 3 O 4 nanourchin, we placed MnO nanourchins surface-modified with carboxylated amphiphilic polysorbate 80 molecules [10] in phosphate-buffered saline (PBS) solutions of various pH values. While the nanourchin is very stable at pH values above 7, the MnO core is easily dissolved at lower pH conditions (pH 4-6) to give a hollow Mn 3 O 4 nanourchin ( Figure S13 in the Supporting Information).…”
mentioning
confidence: 99%
“…MRI has been used to image nanoparticle distribution in a variety of contexts, such as neuroinflammation in root compression (28), soft tissue infection (29), atherosclerosis (30, 31), and angiogenesis in tumor models (32, 33), as well as to confirm SPIO delivery to rabbit liver tumors (8, 34). Recent work in a different rodent model of HCC showed that MRI can quantify both intratumoral uptake of SPIOs after intravenous delivery (17) and labeled NK cells after intra-arterial delivery (35).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified key angiogenic factors, such as basic fibroblast growth factor, interleukin-8, hypoxia-inducible factors, and vascular endothelial growth factor A (VEGFA). Among these, VEGFA and one of its receptors (vascular endothelial growth factor receptor 2, VEGFR2) have been established as the primary proangiogenic factors [11,12]. …”
Section: Introductionmentioning
confidence: 99%